Therapeutic Management of Babesiosis in a Cow: A Case Report - Bante, Shivani; Bagherwal, Rajendra Kumar; Agrawal, Vivek; Rajoriya, Shweta (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Babesiosis is a haemoprotozoan disease intraerythrocytic protozoan parasites of the genus  Babesia that infect a wide range of domestic and wild animals.  It is one of the common tick borne haemoprotozoan diseases  affecting the bovines in tropical and subtropical parts of  Africa, Australia, America, and Asia including India (Kumar and  Kala, 2018). In India, annual economic losses to livestock due  to babesiosis are estimated to be about 57.2 million US dollars  which is mainly caused by two most important species, i.e.,  Babesia bovis and Babesia bigemina (Bock et al., 2004). The  cattle tick Rhipicephalus microplus is the main vector involved  with the transmission and is the only known vector for bovine  babesiosis (Souza et al., 2018). Due to universal distribution of  the ixodid tick, babesiosis is considered as the second most  widespread blood-borne disease of animals (Homer et al., 2000) and is prominently gaining increasing interest as an  emerging zoonosis of humans also (Homer et al., 2000; Zintl  et al., 2003). Clinical symptoms of Babesiosis are classical  haemoglobinuria which is often present, with anaemia and  jaundice that develops especially in more protracted cases  (Bock et al., 2004). The disease has been recorded in all the  cattle breeds but more commonly in exotic and crossbred  cattle than in indigenous ones (Chakrabarti, 2003). The  present communication describes the haemato-biochemical  profile and therapeutic management of a non-descript native  cow with babesiosis infection.
Keywords: Therapeutic; Management; Babesiosis